First report of peritonitis caused by the vancomycin-resistant coccus Pediococcus pentosaceus in a patient on continuous ambulatory peritoneal dialysis. Issue 5 (23rd April 2019) - Gupta, Shefali; Sahu, Chinmoy; Nag, Soumyabrata; Saha, Uma Shankar; Prasad, Narayan; Prasad, Kashi Nath
Abstract : Introduction. Worldwide, about one-tenth of end-stage renal disease (ESRD) patients are on peritoneal dialysis (PD). Peritonitis is a major cause of PD failure and change of therapy to haemodialysis. An update on peritoneal dialysis-related infections has recommended the use of a first generation cephalosporin or vancomycin as an empirical therapy for Gram-positive organisms. Pediococcus spp. is a Gram-positive environmental cocci that have been increasingly reported from various nosocomial infections but very rarely from peritoneal dialysis infections. It is intrinsically resistant to Vancomycin but sensitive to ampicillin. So, diagnosis of this bacteria is important if isolated from PD infections. Case presentation. An elderly female patient of ESRD on continuous ambulatory peritoneal dialysis (CAPD) was admitted with complaints of high fever and cloudy PD effluent for 2 days. She was started with vancomycin and imipenem empirically but did not improve even after 4 days. Pus cells were seen when PD fluid was examined microscopically. BACTEC culture of PD fluid isolated growth of Gram-positive cocci, which was confirmed as Pediococcus pentosaceus . It was resistant to vancomycin. The antibiotic of the patient was changed to ciprofloxacin IV. The patient responded in 2 days and was discharged after 7 days. Conclusion. This is the first case report of Pediococcus pentosaceus peritonitis in an ESRD patient on CAPD. Accurate diagnosis and antibiotic sensitivity test of the bacteria is important especially if isolated in critical patients as it is intrinsically resistant to vancomycin.